Minimizing Total Harmonic Distortion of 7-Level Packed U-Cell Multilevel Inverter Using Whale Optimization Algorithm - Ebrahimi, Faizulddin; Windarko, Novie Ayub; Gunawan, Agus Indra (The Indonesian Journal of Computer Science, 2023)
This paper presents an innovative study introducing a novel design for a single-phase, 7-level inverter. The design combines the modified pulse width modulation (MPWM) technique with the compact packed U-cell (PUC) topology. We evaluate this inverter's performance through comprehensive simulations in the MATLAB Simulink software. Multi-level inverter (MLI) technology is crucial for high-power, medium-voltage energy control. However, using numerous semiconductor switches in traditional MLI setups poses challenges at higher voltage levels, including increased size, costs, and losses. To address these issues, our study proposes a transformative approach, emphasizing reducing active switches within the multi-level inverter architecture. Consequently, we introduce an innovative 7-level PUC-MLI design. This configuration not only reduces harmonic distortion but also addresses cost concerns. Strategically manipulating semiconductor switch sequences significantly enhances the inverter's operational efficiency. A notable contribution is our inventive method to reduce total harmonic distortion (THD) in the inverter's output voltage, achieved through a whale optimization algorithm (WOA). Implementing this algorithm substantially lowers THD levels. Importantly, this approach's effectiveness extends to various inverter topologies and levels, offering a substantial THD reduction without additional expenses.